The combination of mitragynine and morphine prevents the development of morphine tolerance in mice - Fakurazi, Sharida; Abdul Rahman, Shamima; Baharuldin, Mohamad Taufik Hidayat; Ithnin, Hairuszah; Mohd Moklas, Mohamad Aris; Arulselvan, Palanisamy (MDPI, 2013)
Mitragynine (MG) is the major active alkaloid found in Mitragyna speciosa Korth. In the present study, we investigated the enhancement of analgesic action of MG when combined with morphine and the effect of the combination on the development of tolerance towards morphine. Mice were administered intraperitoneally with a dose of MG (15 and 25 mg/kg b.wt) combined with morphine (5 mg/kg b.wt) respectively for 9 days. The antinociceptive effect was evaluated by a hot plate test. The protein expression of cyclic adenosine monophosphate (cAMP) and cAMP response element binding (CREB) was analyzed by immunoblot. Toxicological parameters especially liver and kidney function tests were assessed after the combination treatment with MG and morphine. The concurrent administration of MG and morphine showed significant (p < 0.05) increase in latency time when compared to morphine alone group and the outstanding analgesic effects in the combination regimens were maintained until day 9. For the protein expression, there was a significant increment of cAMP and CREB levels (p < 0.05) in group treated with 5 mg/kg morphine but there was no significant change of these protein expressions when MG was combined with morphine. There was a significant changes in toxicological parameters of various treated groups. The combination treatment of MG and morphine effectively reduce the tolerance due to the chronic administration of morphine.